Insect Juvenile Hormone Mimics: A Chemical Metamorphosis from Terpenoid Esters to Aryloxy-Dioxolanes - Friedrich Karrer; Hartmut Kayser; Hans Peter Buser; Gerardo M. Ramos Tombo (CHIMIA)
The 1,3 dioxolane derivative 5 is a potent juvenile hormone mimic. The stereoselective synthesis of its stereoisomers 6-9 was based on the chiral glycerol derivative 12. Three different approaches to this central compound 12 were investigated: using chiral building blocks, enantioselective catalytic hydrogenation, and stereoselective crystallization. The latter is the most suitable for large scale synthesis. In vivo testing of the different stereoisomers on Nauphoeta cinerea showed that the juvenoid activity is mainly associated with the (2R,4S)-6 isomer.